Estimating the fate of seeds in a Nassella trichotoma population - Lusk, C.S.; Lamoureaux, S.L.; Hurrell, G.A.; Bourd?t, G.W. (New Zealand Plant Protection, 2008)
A previouslydeveloped model for a nassella tussock (Nassella trichotoma) population suggests that 97 of the seeds produced do not enter the soil seed bank To determine the extent to which seeds are lost from the soil surface an experiment was conducted over 1 year at three sites in North Canterbury pastures In January 2007 soil cores with intact pasture in opentopped containers were buried to ground level at each of the sites Three treatments (no seed 25 awned or 25 deawned seeds scattered onto the core surface) were applied The number of intact seeds recovered by monthly exhumation of cores declined linearly and at an average rate of 48 over the year Assuming the model is correct this rate of loss implies that only 5 of the seeds produced reach the soil surface and that 95 are therefore lost before deposition through wind dispersal or through predispersal predation